"FastSchool": A single session of an interprofessional pain management program for chronic pain patients inspired by cognitive behavioral therapy. Issue 12 (December 2022) - Trouvin, Anne-Priscille; Carvès, Sandrine; Rouquette, Alexandra; Coste, Joël; Meyer, Sinja; Colin, Faustine; Deleens, Rodrigue; Medkour, Terkia; Collet, Marie-Pierre; Perrot, Serge; Laroche, Françoise
Abstract: Objectives: Multidisciplinary approaches to treating chronic pain have been proven effective. Currently, chronic pain patients face lengthy waitlists in pain medicine departments. To overcome this problem, we developed the "FastSchool" program to educate patients about pain management and treatment. In this study, we evaluated the benefit of a "FastSchool" session on pain and catastrophizing in chronic pain patients. Methods: Included patients had chronic non-cancer pain, no more than 2 visits to a pain medicine department. Patients attended a single 3-hour session, conducted by an interprofessional team. Four topics were addressed: chronic pain mechanisms, pharmacological therapies, physical activity, and the management of analgesics. Patients completed questionnaires at baseline and at 3 months post-session to assess pain interference, pain intensity, and catastrophizing. Results: The study population included 88 patients; 71 completed the follow-up questionnaires. Pain interference (p = 0.002), average pain intensity (p = 0.013), and catastrophizing (p < 0.001) decreased 3 months after FastSchool. At M3, 35 % of patients felt their pain had improved based on the Patient Global Impression of Change. Conclusion: FastSchool, an innovative short-term educational program inspired by cognitive behavioral therapy, showed positive results in reducing pain impact. Practice implications: Implementation of FastSchool in pain medicine departments would reduce waitlist times for non-pharmacological treatment. Highlights: There is a need for affordable, effective and comprehensive brief interventions in chronic pain management. A single CBT inspired session showed positive results in decreasing pain interference, intensity and catastrophizing. This program is ready to implement by medical and non-medical staff.